2002
DOI: 10.1149/1.1450063
|View full text |Cite
|
Sign up to set email alerts
|

Microstrain and Capacity Fade in Spinel Manganese Oxides

Abstract: With an objective of understanding the differences in the capacity retention behavior of LiMn 2 O 4 and the cation-substituted LiMn 2Ϫy M y O 4 ͑M ϭ Li, Co, and Ni͒ spinel oxides, the peak broadening in the X-ray diffraction patterns on extracting lithium has been analyzed. An analysis of the LiMn 2 O 4 and LiMn 2Ϫy M y O 4 samples before and after treating at room temperature with acid or an oxidizing agent (NO 2 BF 4 ) or at 55°C with electrolyte reveals that the LiMn 2 O 4 system experiences a larger amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 18 publications
3
70
0
1
Order By: Relevance
“…The peak broadening has recently been attributed by our group to the development of microstrain in the LiMn 2 O 4 lattice, which is suppressed by cationic substitutions. 22 It has been reported before by Amatucci et al 15 that the crystallinity decreases proportionately with the percent of capacity loss. The surface/chemical modification of LiMn 2 O 4 appears to suppress the attack by the acidic species present in the electrolyte as well as the occurrence of Jahn-Teller distortion on the surface 9 and thereby leads to better structural integrity with low microstrain and good capacity retention during cycling.…”
Section: Resultsmentioning
confidence: 84%
“…The peak broadening has recently been attributed by our group to the development of microstrain in the LiMn 2 O 4 lattice, which is suppressed by cationic substitutions. 22 It has been reported before by Amatucci et al 15 that the crystallinity decreases proportionately with the percent of capacity loss. The surface/chemical modification of LiMn 2 O 4 appears to suppress the attack by the acidic species present in the electrolyte as well as the occurrence of Jahn-Teller distortion on the surface 9 and thereby leads to better structural integrity with low microstrain and good capacity retention during cycling.…”
Section: Resultsmentioning
confidence: 84%
“…The stresses can arise from anisotropic lattice expansion and contraction upon Li + extraction/insertion, which cause volume variation of the grains. [80] The individual grains in a sintered secondary particle are physically constrained by their neighboring primary particles and stress arising from the anisotropic volume change can cause particle fracture in long term cycle. The differential expansion within a single grain can also contribute to microstrain because a Li + concentration gradient always exists in a primary particle during charge-discharge process.…”
Section: Microstrain and Crack Of Primary Particlesmentioning
confidence: 99%
“…Elevated temperature effects on spinel dissolution.-Many investigations 8,14,[18][19][20][21][22][23] have shown that the dissolution of Mn was accelerated at elevated temperatures leading to a faster capacity fading. Plots of the cyclic voltammogram of three spinel LiMn 2 O 4 disk electrodes in the beaker cell cycled between 3.0 and 4.5 V with 10 mV/s, 500 rpm, and 1 M LiPF 6 ϩ EC/DMC ͑1:1͒ electrolyte, at 30, 45, and 58°C are shown in Fig.…”
Section: Mnmentioning
confidence: 99%
“…14,15 Although many possible factors have been proposed to contribute to the capacity fading of the spinel LiMn 2 O 4 electrode, most of the evidence reported so far points to manganese dissolution at the top of charge as the major reason for the capacity fading. It is essential to investigate the dissolution behavior of the spinel electrode in order to improve the capacity fading of the spinel materials.…”
mentioning
confidence: 99%